The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1094/mpmi-08-18-0227-r
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Two Cellulase Genes in the Gram-Positive Pathogenic Bacterium Clavibacter michiganensis for Wilting in Tomato

Abstract: Diverse plant pathogens secrete cellulases to degrade plant cell walls. Previously, the plasmid-borne cellulase gene celA was shown to be important for the virulence of the gram-positive bacterium Clavibacter michiganensis in tomato. However, details of the contribution of cellulases to the development of wilting in tomato have not been well-determined. To better understand the contribution of cellulases to the virulence of C. michiganensis in tomato, a mutant lacking cellulase activity was generated and compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 35 publications
3
43
0
Order By: Relevance
“…Like plant expansins, no microbial expansins have been documented to have enzymatic activity (Jahr et al, 2000;Laine et al, 2000;Olarte-Lozano et al, 2014;Georgelis et al, 2015;Cosgrove, 2017;Tancos et al, 2018). The evolutionary history, taxonomic distribution, mechanism(s) of action and ecological function(s) of microbial expansins remain enigmatic in non-Plantae genetic backgrounds, and there is currently no framework for predicting their functional roles (Jahr et al, 2000;Saloheimo et al, 2002;Brotman et al, 2008;Georgelis et al, 2015;Junior et al, 2015;Hwang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Like plant expansins, no microbial expansins have been documented to have enzymatic activity (Jahr et al, 2000;Laine et al, 2000;Olarte-Lozano et al, 2014;Georgelis et al, 2015;Cosgrove, 2017;Tancos et al, 2018). The evolutionary history, taxonomic distribution, mechanism(s) of action and ecological function(s) of microbial expansins remain enigmatic in non-Plantae genetic backgrounds, and there is currently no framework for predicting their functional roles (Jahr et al, 2000;Saloheimo et al, 2002;Brotman et al, 2008;Georgelis et al, 2015;Junior et al, 2015;Hwang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The gh5 domain in Enterobacteriaceae is non-homologous to the GH5 domain in Xanthomonadaceae, and the exlx and gh5 domain structure in some Enterobacteriaceae is in reverse orientation compared to the gh5-exlx domain order in Xanthomonadaceae. A distinct gh5 domain that is truncated to 289 amino acids is found in Clavibacter michiganensis ( CelA ), and this is the only known microbial expansin that is fused to both a GH5 and CBM2 domain in a single coding sequence (27). This suggests there have been at least three independent origins of an expansin adjacent or fused to a gh5 family functional domain in bacterial plant pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…CelA is considered to have an essential role in virulence. Several studies (Meletzus et al , 1993; Thapa et al , 2017; Hwang et al , 2019) showed that nonpathogenic mutant strains lacking celA restored their pathogenicity when the gene was reincorporated. However, in New York State and Uruguay 6% and 2.5% of the strains, respectively, did not amplify celA even though they were pathogenic (Tancos et al , 2015; Croce et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The PI contains genes coding for serine proteases (e.g., chpC , chpG , and ppaA ), important for host plant colonization, and a tomatinase ( tomA ), which putatively deactivates the plant immune system (Eichenlaub and Gartemann, 2011). Plasmids pCM1 and pCM2 carry genes coding for the endo‐β‐1,4‐glucanase CelA and the serine protease Pat‐1, respectively, which are critical factors for bacterial pathogenicity (Dreier et al , 1997; Hwang et al , 2019). Strains lacking either of these two genes are less virulent or nonpathogenic (Meletzus et al , 1993; Kleitman et al , 2008; Milijašević‐Marčić et al , 2012; Tancos et al , 2015).…”
Section: Introductionmentioning
confidence: 99%